ANALISIS PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN GULA JAHE ALAMI SUCENJURUTENGAH - Bachtiar, Danis Imam; Bachtiar, Firman (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The rapid development of information and communication technology has changed the pattern of people's buying culture from offline to online. Finally, the product marketing strategy must also follow changes in the community, including the marketing of MSME products in Purworejo Regency. This research was conducted to find out more about the effect of social media promotion and electronic word of mouth (e-WoM) on buying interest of MSME products in Purworejo Regency at Yodotuku.com, either partially or simultaneously. The number of samples is 112 respondents selected by purposive sampling method. The instrument test uses validity and reliability tests. Data analysis technique using multiple linear regression. The results of the study showed that promotion through Instagram had a positive but not significant effect on the intention to buy MSME products in Purworejo Regency at Yodotuku.com. Meanwhile, e-WoM has a positive effect on consumer buying interest. Based on the test results, it is also known that simultaneously there is a positive and significant influence between promotions through social media Instagram and e-WoM on the buying interest of MSME products in Purworejo Regency at Yodotuku.com. Therefore promotions on Instagram social media in the form of positive testimonials and reviews from consumers will be more optimal to influence buying interest for MSME products